A gel-forming clusteroluminogenic polymer with tunable emission behavior as a sustained-release carrier enabling real-time tracking during bioactive agent delivery. (December 2020) - Lai, Wing-Fu; Huang, Eric M.; Wong, Wing-Tak
Highlights: CT is a non-conjugated luminescent polymer derived from cellulose. Tunable microstructures of CT enable controlled release of bioactive agents. CT displays clusterization-induced emission for use in self-illuminating therapy. Solutions of CT can form gels in situ via molecular entanglement. In situ gelation of CT can be tracked in real time in a living body after injection. Abstract: Sustained-release carriers with intrinsic luminescence exhibit the potential to combine imaging with bioactive agent delivery in practice. This study reports the synthesis and properties of CT, which is a gel-forming and highly tunable non-conjugated polymer with intrinsic luminescence. Owing to the excitation wavelength-dependent emission tunability of CT, optical imaging can be performed in a wide range of excitation wavelengths. This study is the first proof-of-concept study successfully integrating the property of clusterization-triggered emission into carrier design for combining imaging with bioactive agent delivery. By using cancer therapy as a practical example, our results demonstrate that CT is a depot system that cannot only enhance in vivo antitumor efficacy but can also allow its location and gelation process to be tracked in real time by giving an intrinsic blue-colored fluorescence signal. Together with its high biocompatibility, CT shows high practical potential for executing self-illuminating therapy to tackle cancer. Graphical abstract: Image, graphical abstract